(untitled) (International Journal of Environmental Sciences, 2025)
The field of education policy movement research about policy transfer and adaptation across contextual boundaries is witnessing ongoing growth. Research on the education policy movement keeps advancing through educators’ work that builds upon established frameworks and produces new theories, which sometimes merge with existing research. The theoretical bases, along with assumptions which sustain this field, remain implicit and under-investigated. The theoretical and methodological limitations in existing studies are addressed through a discussion of four main educational policy movement study approaches, which include cross-dimensional analysis, discourse-centred research, policy mobilities methodology and decolonial perspectives. The analysis reviews theoretical aspects together with methodological strengths of various approaches for implementing innovative strategies for policy development and analysis for inclusive education. The paper provides an understanding of education policy movement through the lens of globalisation before moving to its analytical perspectives. The methodology includes a qualitative review of secondary sources including global documents, academic literature and comparative studies. The analysis investigates various worldwide political, economic and cultural forces that influence inclusive education policy reforms by enabling or obstructing implementation across six Asia-Pacific nations. The establishment of this contextual discussion sets a pathway for the wider framework through which policy movement and research respond to global policy interpretation and adaptation.